Why America lost the war on poverty-- and how to win it - Stricker, Frank (University of North Carolina Press, 2007)
Analyzing the War on Poverty, theories of the culture of poverty and the underclass, the effects of Reaganomics, and the 1996 welfare reform, Stricker demonstrates that most antipoverty approaches are futile without the presence (or creation) of good jobs. He argues that a serious public debate is needed about the job situation; social programs must be redesigned, a national health care program must be developed, and economic inequality must be addressed.